Polypropylene Coating Composition

A metallocene-catalyzed propylene random copolymer with controlled site defects addresses the issues of hexane extractability and thermal stability in polypropylene compositions, enhancing sealing and thermal stability for extrusion coatings in demanding applications.

JP7605863B2Active Publication Date: 2024-12-24BOREALIS AG
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
JP2022572485
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-05-27
Filing Date
2021-05-26
Publication Date
2024-12-24
Estimated Expiration
2041-05-26

AI Technical Summary

Technical Problem

Existing polypropylene compositions for extrusion coatings have high hexane extractability, poor thermal stability, and inadequate sealing properties, limiting their use in high-demand applications such as medical and food packaging, particularly in processes requiring high melt flow rates and sterilization.

Method used

A polypropylene composition comprising a propylene random copolymer produced using a metallocene catalyst, with controlled site defects and specific molecular characteristics, including a melt flow rate of 15-40 g/10min, melting temperature of 115-145°C, and low hexane extractables, ensuring improved sealing and thermal stability.

Benefits of technology

The composition exhibits enhanced sealing properties and thermal stability, making it suitable for high-speed extrusion coating of various substrates, including food packaging, with reduced hexane extractables and improved hot tack performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007605863000006
    Figure 0007605863000006
  • Figure 0007605863000007
    Figure 0007605863000007
  • Figure 0007605863000001
    Figure 0007605863000001
Patent Text Reader

Abstract

The present invention provides a polymer having a melt flow rate MFR2 (230°C / 2.16 kg) of 15 to 40 g / 10 min measured according to ISO 1133, a melting temperature T of 115 to 145°C measured by DSC according to ISO 11357, m , and 13 The present invention relates to a polypropylene composition comprising a propylene random copolymer having 0.01 to 1.2 mole percent of 2,1-site defects and 3,1-site defects as measured by C NMR, an article coated with the composition, a method for coating an article with the composition, and a use of the composition for coating an article.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a propylene random copolymer suitable for extrusion coating, a coated article having a layer comprising said propylene random copolymer, a method for coating an article using said propylene random copolymer and the use of said propylene random copolymer for coating an article. [Background technology]

[0002] Generally, extrusion coating of substrates such as paper, paperboard, fabrics, metal foils, etc. with thin layers of plastics is carried out on a large scale. The coating composition is extruded in a first step where a flux of molten polymeric material passes through a flat die to obtain a film with a thickness of a few microns. In the second step, the coating step, the film is placed on a support and passes over a cooling cylinder. When cooled, the polymer adheres to the support. High speed extrusion coating requires a relatively high melt flow rate MFR of 10 g / 10 min or more. 2 A description of the extrusion coating process is given, for example, in RA V Raff and KW Doak, Crystalline Olefin Polymers, Part II (Interscience Publishers, 1964), pp. 478-484, or in Vieweg, Schley and Schwarz: Kunststoff Handbuch, Band IV, Polyolefine, Carl Hanser Verlag (1969), 20, pp. 412-420.

[0003] US Patent No. 3,418,396 discloses a polypropylene / polyethylene composition for extrusion coating with a high melt flow rate. The polypropylene used is disclosed to have a high degree of hexane extractables, which is undesirable, especially for coating articles for food applications. Furthermore, the presence of polyethylene reduces the composition's ability to withstand high temperatures. However, in some food applications, such as retort pouches, or in some medical applications, sterilization is required, which requires sufficient heat stability of the extrusion coating.

[0004] EP 2999721 discloses propylene random copolymers with high melt flow rates produced in the presence of Ziegler-Natta catalysts. These propylene random copolymers also have a relatively high degree of hexane extractables. Furthermore, EP 2999721 does not relate specifically to extrusion coating, and the sealing properties of the copolymers, such as hot tack force and hot tack temperature, still need to be improved.

[0005] Propylene random copolymers can also be produced using single-site catalysts such as metallocene catalysts, however, the high melt flow rates required for extrusion coating are usually achieved by controlled rheology, i.e., post-production treatment of the polypropylene to increase the melt flow rate, such as by the use of peroxides or radiation.

[0006] WO 2012 / 109449 discloses controlled rheology formulations containing high melt strength polypropylene for extrusion coating based on a radiation modification process. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] U.S. Patent No. 3,418,396 [Patent Document 2] European Patent No. 2999721 [Patent Document 3] International Publication No. 2012 / 109449 Summary of the Invention

[0008] However, these modifications result in significant degradation of the polypropylene, for example causing the formation of gels, thus limiting the use of the polypropylene compositions in demanding applications, such as in the medical field.

[0009] Thus, there remains a need for improved propylene polymer compositions that have improved sealing and hot tack properties, have low gel content, can withstand high temperatures, and are suitable for extrusion coating of a wide variety of substrates, which compositions should not require the addition of processing aids such as LDPE or the use of rheology control materials to achieve these properties.

[0010] The present invention relates to Melt flow rate (MFR) of 15~40g / 10min measured according to ISO 1133 2 (230℃ / 2.16kg) Melting temperature T of 115~145℃ measured by DSC according to ISO 11357 m , and · 13 The number of 2,1 site defects and 3,1 site defects, between 0.01 and 1.2 mol %, as measured by C NMR The present invention provides a polypropylene composition comprising or consisting of a propylene random copolymer having [Brief description of the drawings]

[0011] [Figure 1] 1 is a sealing curve for Example 1 of the present invention (IE1). [Diagram 2] 1 is a sealing curve of Comparative Example 2 (CE2). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The polypropylene composition of the present invention is well suited for high speed extrusion coating, exhibits improved sealing properties, and results in coatings having low hexane extractables such that the coated articles may be used in food packaging.

[0013] There can be three different types of regiodefects in propylene polymers: 2,1-erythro defects (2,le), 2,1-threo defects (2,It) and 3,1 defects. A detailed description of the structure and formation mechanism of regiodefects in polypropylene can be found in Chemical Reviews 2000, 100(4), pp. 1316-1327. These defects, as explained in detail below, 13 It is measured using C NMR.

[0014] The term "2,1 site defects" as used herein defines the sum of 2,1-erythro site defects and 2,1-threo site defects.

[0015] Propylene random copolymers having the number of site defects as required for the propylene composition of the present invention are usually prepared in the presence of a preferably single-site catalyst.

[0016] The catalyst especially influences the microstructure of the polymer. Thus, polypropylene prepared using metallocene catalysts offers a different microstructure compared to polypropylene prepared using Ziegler-Natta (ZN) catalysts. The most significant difference is the presence of site defects in metallocene-produced polypropylene, which is not the case for Ziegler-Natta (ZN)-produced polypropylene.

[0017] Preferably, the number of 2,1 site defects and 3,1 site defects in the propylene random copolymer is 13 It is 0.1 to 1.0 mol %, more preferably 0.2 to 0.9 mol %, as measured by C NMR.

[0018] The composition of the present invention is characterized in that at least 80% by weight of propylene random copolymer, more preferably at least 90% by weight of propylene random copolymer, most preferably propylene random copolymer is the only polymer component present in the composition, i.e. the polypropylene composition consists of propylene random copolymer, and optionally contains one or more additives as described herein below.The amount of additives, if present, is usually 5% by weight or less, preferably 3% by weight or less.

[0019] Propylene random copolymers such as those contained in the composition of the present invention have a melt flow rate MFR measured according to ISO 1133 2 (230° C. / 2.16 kg) is preferably 17 to 35 g / 10 min, and even more preferably 20 to 30 g / 10 min.

[0020] Also, the melting temperature T of propylene random copolymers determined by DSC according to ISO 11357 m The heating temperature is preferably 120 to 148°C, and even more preferably 122 to 135°C.

[0021] Furthermore, the propylene random copolymer preferably has a relatively narrow molecular weight distribution as determined by GPC. Thus, the propylene random copolymer preferably has a molecular weight distribution MWD of 2.4 to 5.5, more preferably 2.5 to 4.5, and even more preferably 2.7 to 4.0.

[0022] Furthermore, the propylene random copolymer has the advantage of having a low hexane extractable content.Accordingly, the propylene random copolymer has a hexane extractable content of less than 2.0% by weight, more preferably less than 1.5% by weight, as measured according to the FDA test.

[0023] Preferably, the propylene random copolymer is an ethylene propylene random copolymer, ie preferably consisting of propylene and ethylene monomer units.

[0024] More preferably in this embodiment, the propylene random copolymer has an ethylene content in the range of 2.0 to 5.5 wt%, more preferably in the range of 2.1 to 5.0 wt%, even more preferably in the range of 2.2 to 4.5 wt%, and most preferably in the range of 2.5 to 4.0 wt%.

[0025] For ease of processing, it is also desirable for the random propylene copolymer to have an adequate crystallization temperature even in the absence of a nucleating agent.

[0026] Thus, preferably, the propylene random copolymer has a crystallization temperature Tc in the range of 75 to 100°C, more preferably in the range of 80°C to 105°C, for example in the range of 82°C to 100°C, determined by DSC according to ISO 11357.

[0027] The propylene random copolymers preferably have a xylene cold soluble (XCS) fraction, determined according to ISO 16152, of 0.1 to less than 15 wt. %, more preferably 0.2 to 10 wt. %, most preferably 0.5 to 7.5 wt. %.

[0028] Furthermore, the propylene random copolymer preferably has a flexural modulus, determined according to ISO 178 on injection moulded specimens, in the range of 500 to 1000 MPa, more preferably in the range of 550 to 950 MPa, most preferably in the range of 600 to 900 MPa.

[0029] Preferably, the propylene random copolymer comprises or consists of two polymer fractions (RACO-1) and (RACO-2). The ratio between fraction (RACO-1) and fraction (RACO-2) is preferably 30:70 to 70:30, more preferably 45:55 to 65:35, and most preferably 55:45 to 60:40.

[0030] Optionally, small amounts of prepolymer, usually less than 5% by weight, may be present in the random propylene copolymer.

[0031] In embodiments where the random propylene copolymer is an ethylene propylene copolymer, preferably (RACO-1) has an ethylene content in the range of 1.5 to 5.5 wt%, more preferably 2.0 to 5.0 wt%, most preferably 2.5 to 4.0 wt%, and / or preferably (RACO-2) has an ethylene content in the range of 2.0 to 6.0 wt%, more preferably 2.5 to 5.5 wt%, most preferably 3.0 to 5.0 wt%.

[0032] Preferably, the ethylene content of fraction (RACO-1) is lower than the ethylene content of fraction (RACO-2).

[0033] Additionally, (RACO-1) is the melt flow rate (MFR) measured according to ISO 1133 2 (230°C / 2.16 kg) is in the range of 3.0 to 20.0 g / 10 min, more preferably 5.0 to 17.0 g / 10 min, and most preferably 7.0 to 15.0 g / 10 min, and / or (RACO-2) is the melt flow rate MFR 2 (230° C. / 2.16 kg) is preferably in the range of 5.0 to 50.0 g / 10 min, more preferably 10 to 40 g / 10 min, and most preferably 15 to 30 g / 10 min.

[0034] Preferably, the random propylene copolymer is produced in the presence of a metallocene catalyst, preferably a metallocene catalyst comprising a complex in any one of the embodiments described in WO 2013 / 007650, WO 2015 / 158790 and WO 2018 / 122134.

[0035] To form an active catalytic species, it is usually necessary to use a cocatalyst, which is well known in the art. Cocatalysts containing one or more compounds of Group 13 metals, such as organoaluminum compounds or boron-containing cocatalysts or combinations thereof, used to activate metallocene catalysts are suitable for use in the present invention.

[0036] In a preferred embodiment of the present invention, a cocatalyst system is used that includes a boron-containing cocatalyst, such as a borate cocatalyst and an aluminoxane cocatalyst.

[0037] Suitable cocatalysts are described in WO 2013 / 007650, WO 2015 / 158790 and WO 2018 / 122134, and it is preferred that a cocatalyst of any one of the embodiments as described therein is used.

[0038] The catalyst system used to prepare the random propylene copolymers of the present invention is ideally provided in the form of solid particulates supported on an external support.

[0039] The particulate support material used is silica or a mixed oxide such as silica-alumina. It is preferred to use a silica support.

[0040] Particularly preferably, the support is a porous material such that the complexes can be loaded into the pores of the particulate support, for example using processes similar to those described in WO 94 / 14856, WO 95 / 12622 and WO 2006 / 097497.

[0041] The preparation of solid catalyst systems is also described in WO 2013 / 007650, WO 2015 / 158790 and WO 2018 / 122134, and preferably the catalyst system is prepared according to any one of the embodiments described therein.

[0042] The random propylene copolymer in any of the embodiments comprising two fractions (RACO-1) and (RACO-2) preferably has the following: a) polymerizing propylene and a comonomer, preferably ethylene, in a first reactor (R1) to obtain a polymer fraction (RACO-1); b) transferring said polymer fraction (RACO-1) and unreacted comonomer from said first reactor to a second reactor (R2); c) feeding propylene and a comonomer, preferably ethylene, to the second reactor (R2); d) polymerizing in said second reactor (R2) propylene and comonomers in the presence of said polymer fraction (RACO-1) to obtain a polymer fraction (RACO-2) intimately mixed with (RACO-1), resulting in a final propylene random copolymer; wherein preferably the polymerization is carried out in the presence of a metallocene catalyst system, in any one of the embodiments described herein.

[0043] Thus, the propylene random copolymers are preferably prepared by polymerizing propylene and a comonomer, preferably ethylene, in the presence of a metallocene catalyst by a sequential polymerization process comprising or consisting of at least two reactors connected in series.

[0044] Each of the two polymerization stages can be carried out in solution, slurry, fluidized bed, bulk or gas phase.

[0045] The term "polymerization reactor" is intended to indicate that the main polymerization takes place therein. Thus, if the process consists of one or two polymerization reactors, this definition does not exclude the option that the whole system comprises a prepolymerization step, for example in a prepolymerization reactor. The term "consists of" is merely a closed expression from the point of view of the main polymerization reactor.

[0046] The term "sequential polymerization process" indicates that the propylene random copolymer is produced in at least two reactors connected in series. Thus, such a polymerization system includes at least a first polymerization reactor (R1) and a second polymerization reactor (R2), and optionally a third polymerization reactor (R3).

[0047] The first polymerization reactor (R1) is preferably a slurry reactor and can be any continuous or simple stirred batch tank reactor or loop reactor operating in bulk or slurry. By bulk it is meant polymerization in a reaction medium containing at least 60% (w / w) of monomer. According to the invention the slurry reactor is preferably a (bulk) loop reactor.

[0048] The second polymerization reactor (R2) and the optional third polymerization reactor (R3) are preferably gas phase reactors (GPR), i.e. the first gas phase reactor (GPR1) and the second gas phase reactor (GPR2). The gas phase reactors (GPR) according to the present invention are preferably fluidized bed reactors, fast fluidized bed reactors or settled bed reactors, or any combination thereof.

[0049] A preferred multi-stage process is the "loop gas phase" process (known as BORSTAR® technology) as developed by Borealis, as described in patent applications such as EP 0 887 379, WO 92 / 12182, WO 2004 / 000899, WO 2004 / 111095, WO 99 / 24478, WO 99 / 24479 or WO 00 / 68315.

[0050] A more suitable slurry gas phase process is Basell's Spheripol® process.

[0051] Preferably, in the above defined process for producing propylene random copolymers (RACO), the conditions in the first reactor (R1) of step (a), i.e. the slurry reactor (SR) such as the loop reactor (LR), may be as follows: The temperature is within the range of 40°C to 110°C, preferably 60°C to 100°C, and more preferably 65°C to 95°C. The pressure is in the range of 20 bar to 80 bar, preferably 40 bar to 70 bar. Hydrogen can be added to control the molar mass in a manner known per se.

[0052] The reaction mixture of the first reactor (R1) is then transferred to the second reactor (R2), ie the gas phase reactor (GPR1), the conditions of which are preferably as follows: The temperature is within the range of 50°C to 130°C, preferably 60°C to 100°C. The pressure is in the range of 5 bar to 50 bar, preferably 15 bar to 35 bar. Hydrogen can be added to control the molar mass in a manner known per se.

[0053] The polypropylene composition of the present invention may contain one or more conventional additives selected from the group including slip agents, antiblock agents, UV stabilizers, antistatic agents, α-nucleating agents and antioxidants, preferably in a total amount of up to 0.01-5.0 wt%, more preferably 0.05-3.0 wt%.

[0054] Slip agents migrate to the surface and act as polymer-polymer lubricants and polymer-to-metal roller lubricants, resulting in a lower coefficient of friction (CoF). Examples are fatty acid amides such as erucamide (CAS No. 112-84-5), oleamide (CAS No. 301-02-0), stearamide (CAS No. 124-26-5) or combinations thereof.

[0055] Examples of antioxidants are sterically hindered phenols (e.g. CAS number 6683-19-8, also sold by BASF as Irganox 1010 FF (trade name)), phosphorus-based antioxidants (e.g. CAS number 31570-04-4, also sold by Clariant as Hostanox PAR 24 (FF) (trade name) or by BASF as Irgafos 168 (FF) (trade name)), sulfur-based antioxidants (e.g. CAS number 693-36-7, sold by BASF as Irganox PS-802 FL (trade name)), nitrogen-based antioxidants (e.g. 4,4'-bis(1,1'-dimethylbenzyl)diphenylamine) or mixtures of antioxidants.

[0056] Examples of acid scavengers are calcium stearate, sodium stearate, zinc stearate, magnesium oxide and zinc oxide, synthetic hydrotalcites (e.g. SHT, CAS number 11097-59-9), lactates and lactylates, as well as calcium stearate (CAS number 1592-23-0) and zinc stearate (CAS number 557-05-1).

[0057] Common antiblocking agents include natural silicas such as diatomaceous earth (e.g., CAS No. 60676-86-0 (SuperfFloss), CAS No. 60676-86-0 (SuperFloss E), or CAS No. 60676-86-0 (Celite 499)), synthetic silicas (e.g., CAS No. 7631-86-9, CAS No. 7631-86-9, CAS No. 7631-86-9, CAS No. 7631-86-9, CAS No. 7631-86-9, CAS No. 112926-00-8, CAS No. 7631-86-9, or CAS No. 7631-86-9), silicates (e.g., aluminum silicate (kaolin), CAS No. 1318-74-7, aluminum silicate), sodium triphosphate, CAS number 1344-00-9, calcined kaolin, CAS number 92704-41-1, aluminum silicate, CAS number 1327-36-2, or calcium silicate, CAS number 1344-95-2), synthetic zeolite (sodium calcium aluminosilicate hydrate, CAS number 1344-01-0, or sodium calcium aluminosilicate hydrate, CAS number 1344-01-0).

[0058] Suitable UV stabilizers are, for example, bis-(2,2,6,6-tetramethyl-4-piperidyl)-sebacate (CAS number 52829-07-9, Tinuvin 770), 2-hydroxy-4-n-octoxy-benzophenone (CAS number 1843-05-6, Chimassorb 81).

[0059] Alpha nucleating agents such as sodium benzoate (CAS number 532-32-1); a mixture of aluminum-hydroxy-bis[2,2'-methylene-bis(4,6-di-t-butylphenyl)phosphate] and lithium myristate (available as Adekastab NA-21 from Adeka Palmarol, France) or 1,3:2,4-bis(3,4-dimethylbenzylidene)sorbitol (CAS number 135861-56-2, available as Millad 3988 from Milliken, USA) may also be added.

[0060] Suitable antistatic agents are, for example, glycerol esters (CAS number 97593-29-8) or ethoxylated amines (CAS numbers 71786-60-2 or 61791-31-9) or ethoxylated amides (CAS number 204-393-1).

[0061] Typically, these additives are added in amounts of 100 to 1,000 ppm for each single component.

[0062] Preferably, at least an antioxidant is added to the composition of the present invention.

[0063] Unless otherwise indicated, the description of the present invention should be understood as being such that any one or more of the preferred embodiments of the compositions of the present invention described above can be combined with the invention described in its most general characteristics.

[0064] The present invention further relates to a coated article having a coating layer comprising or consisting of the polypropylene composition according to any of the above-mentioned embodiments, and to a method for coating an article, in which the polypropylene composition according to any of the above-mentioned embodiments is coated onto the article by extrusion.

[0065] The extrusion coating method can be carried out using conventional extrusion coating techniques. The composition according to the present invention may therefore typically be fed into an extrusion device in the form of pellets. The polymer melt from the extruder is preferably passed through a flat die onto the substrate to be coated. The coated substrate is cooled on a chill roll and then sent to an edge trimmer for winding.

[0066] The width of the die usually depends on the size of the extruder used. Thus, for a 90 mm extruder, the width is preferably in the range of 600-1200 mm, for a 115 mm extruder, 900-2500 mm, for a 150 mm extruder, 1000-4000 mm, and for a 200 mm extruder, 3000-5000 mm. The line speed (drawdown speed) is preferably 75 m / min or more, more preferably 100 m / min or more. For most commercially operating machines, the line speed is preferably more than 300 m / min or more than 500 m / min. Modern machines are designed to operate at line speeds of up to 1,000 m / min, for example 300-800 m / min.

[0067] The temperature of the polymer melt is typically 240-330°C. The polypropylene composition of the present invention can be extruded onto a substrate as a single layer coating or as an outer layer in a coextrusion process. In a multi-layer extrusion coating, the polymer layer structure as defined above and optionally other polymer layers can be coextruded. If desired or necessary, ozone treatment and / or corona treatment can be further carried out in a known manner.

[0068] The primary end uses for extrusion coated products and articles obtained using the compositions according to the invention are packaging applications such as liquid packaging for milk, juice, wine or other liquids, flexible packaging for snacks, confectionery, meat, cheese and medical products, detergent cartons, cups and dish trays for ovens or microwaves, or sterilizable food packaging, as well as industrial applications such as photo paper or paper reels and reem wraps, and technical laminates, preferably with sterilizable and / or retortable properties.

[0069] Furthermore, the present invention relates to the use of the polypropylene composition according to any of the above mentioned embodiments for extrusion coating of an article.

[0070] The article can be any article onto which a coating can be applied by extrusion coating, such as a fibrous substrate such as paper, paperboard or kraft paper or a woven or nonwoven fabric, a metal foil such as an aluminum foil, or a plastic film such as an oriented polypropylene film, a non-oriented polypropylene film, a PET film, a PA film or a cellophane film, a metallized film or a combination thereof.

[0071] Preferably, the article is paper, paperboard, a textile substrate, and / or a metal foil.

[0072] In the following, the measurement and determination methods of the parameters used in this specification are presented and the invention is further explained by means of examples and comparative examples with reference to the drawings.

[0073] <Measurement and determination methods> a) Calculation of the comonomer content of the second polymer fraction (RACO-2)

[0074]

number

[0075] Where: w(A-1) is the weight fraction of the first polymer fraction (RACO-1) [wt.%], w(A-2) is the weight fraction of the second polymer fraction (RACO-2) [wt %], C(A-1) is the comonomer content [wt.%] of the first polymer fraction (RACO-1), C(A) is C 2 C 3 is the comonomer content [wt%] of the random copolymer (RACO), C(A-2) is the calculated comonomer content [wt %] of the second polymer fraction (RACO-2).

[0076] b) Melt flow rate (MFR) 2 Measurement MFR 2 (230°C) is measured in accordance with ISO 1133 (230°C, 2.16 kg load).

[0077] c) Melt flow rate MFR of polymer fraction (RACO-2) 2 Calculation

[0078]

number

[0079] Where: w(A1) is the weight fraction of the polymer fraction RACO-1 [wt%], w(A2) is the weight fraction of the polymer fraction RACO-2 [wt%], MFR(A1) is the melt flow rate (MFR) of polymer fraction RACO-1 2 (230°C) [g / 10 min], MFR(A) is the melt flow rate (MFR) of the entire random propylene copolymer (RACO). 2 (230°C) [g / 10 min], MFR(A2) is the calculated melt flow rate MFR of polymer fraction RACO-2 2 (230℃) [g / 10min].

[0080] d) Quantification of microstructure by NMR spectroscopy Quantitative nuclear magnetic resonance (NMR) spectroscopy was further used to quantify the comonomer content and comonomer sequence distribution of the polymers. 13 C{ 1 The H}NMR spectrum 1 H and 13All spectra were recorded in solution using a Bruker Advance III 400 NMR spectrometer operating at 400.15 MHz and 100.62 MHz for C, respectively. 13 All gases were recorded at 125 °C using a 10 mm extended temperature probe head optimized for C, with nitrogen gas as the gas of choice. Approximately 200 mg of material was dissolved in 3 ml of 1,2-tetrachloroethane-d 2 (TCE-d 2 ) to chromium (III) acetylacetonate (Cr(acac) 3 ) to give a 65 mM solution of the relaxation agent in the solvent (Singh, G., Kothari, A., Gupta, V., Polymer Testing 28 5 (2009), 475). After initial sample preparation in a heat block to obtain a homogenous solution, the NMR tube was further heated in a rotating oven for at least 1 h. After insertion in the magnet, the tube was spun at 10 Hz. This setting was chosen primarily for the high resolution and quantitativeness required to accurately quantify the ethylene content. Standard single pulse excitation without NOE was employed with optimized tip angle, 1 second recycle delay, and bilevel WALTZ16 decoupling scheme (Zhou, Z., Kuemmerle, R., Qiu, X., Redwine, D., Cong, R., Taha, A., Baugh, D., Winniford, B., J. Mag. Reson. 187 (2007) 225; Busico, V., Carbonniere, P., Cipullo, R., Pellecchia, R., Severn, J., Talarico, G., Macromol. Rapid Commun. Rapid Commun. 2007, 28, 1128). A total of 6144 (6k) transients were acquired per spectrum.

[0081] quantitative 13 C{ 1The {H} NMR spectra were processed and integrated using a proprietary computer program, and the relevant quantitative properties were determined from the integrals. All chemical shifts were indirectly referenced to the central methylene group (EEE) of the ethylene block at 30.00 ppm using the chemical shift of the solvent. This method allowed for comparative reference even in the absence of this structural unit. Characteristic signals corresponding to the incorporation of ethylene were observed (Cheng, HN, Macromolecules 17 (1984), 1950).

[0082] Because characteristic signals corresponding to 2,1 erythro site defects were observed (see L. Resconi, L. Cavallo, A. Fait, F. Piemontesi, Chem. Rev. 2000, 100(4), 1253; Cheng, HN, Macromolecules 1984, 17, 1950; and WJ. Wang and S. Zhu, Macromolecules 2000, 33 1157), it was necessary to correct for the effect of site defects on the measured properties. No characteristic signals corresponding to other types of site defects were observed.

[0083] The comonomer fraction is 13 C{ 1 Quantification was performed using the method of Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157) through integration of multiple signals over the entire spectral range of the {H} spectrum. This method was chosen for its robustness and ability to take into account the presence of regio-defects when necessary. The integration region was slightly adjusted to increase applicability over the entire range of comonomer contents encountered.

[0084] For systems in which only isolated ethylene in the PPEPP sequence is observed, we modified the method of Wang et al. to reduce the effect of non-zero integrals of sites known to be absent. This approach reduces the overestimation of ethylene content in such systems, accomplished by reducing the number of sites used to determine absolute ethylene content as follows: E=0.5(Sββ+Sβγ+Sβδ+0.5(Sαβ+Sαγ)) Using this set of sites, the corresponding integral equation becomes: E = 0.5(I H +I G +0.5(I C +I D )) Here we use the same notation as used in the paper by Wang et al. (Wang, WJ., Zhu, S., Macromolecules 33 (2000), 1157). The equation used for absolute propylene content was unchanged.

[0085] The mole percent of comonomer incorporation was calculated from the mole fractions. E[mol%]=100*fE

[0086] The weight percent of comonomer incorporation was calculated from the mole fraction. E[weight%]=100*(fE*28.06) / ((fE*28.06)+((1-fE)*42.08))

[0087] Comonomer sequence distribution at the triad level was determined using the analytical method of Kakugo et al. (Kakugo, M., Naito, Y., Mizunuma, K., Miyatake, T. Macromolecules 15 (1982) 1150.) This method was chosen for its robustness and the integral region was slightly adjusted to increase applicability to a wider range of comonomer contents.

[0088] e) Xylene solubles (XCS, wt%) The xylene soluble (XS) fraction as defined and described in this invention was determined according to ISO 16152 as follows: 2.0 g of polymer was dissolved in 250 ml of p-xylene at 135° C. under stirring. After 30 minutes, the solution was cooled at ambient temperature for 15 minutes and then left to stand at 25±0.5° C. for 30 minutes. The solution was filtered through filter paper and placed into two 100 ml flasks. The solution in the first 100 ml container was evaporated in a nitrogen stream and the residue was dried under vacuum at 90° C. until a constant weight was reached. The xylene soluble fraction (%) can then be determined as follows: XS%=(100*m*V0) / (m0*v) m0 = initial polymer amount (g) m = weight of residue (g) V0 = initial volume (ml) v = volume of sample analyzed (ml)

[0089] f) DSC analysis, melting temperature (Tm) and crystallization temperature (Tc) Data were measured on 5-7 mg samples using a TA Instrument Q2000 Differential Scanning Calorimeter (DSC) performed in a heat / cool / heat cycle at a scan rate of 10 °C / min in the temperature range of -30 to +225 °C according to ISO 11357 / Part 3 / Method C2.

[0090] The crystallization temperature (Tc) and crystallization enthalpy (Hc) are determined from the cooling step, and the melting temperature (Tm) and melting enthalpy (Hm) are determined from the second heating step.

[0091] g) Flexural modulus Flexural modulus is measured for injection molded 80 x 10 x 4 mm according to EN ISO 1873-2 3 is determined according to ISO 178 for test bars.

[0092] h) Hexane extract Hexane extractability is measured according to federal registration, Title 21, Chapter 1, Part 177, Section 1520, Appendix B, on a 100 μm thick cast film produced on a monolayer cast film line with a melt temperature of 220° C. and a chill roll temperature of 20° C. The extraction was performed at a temperature of 50° C. and an extraction time of 30 minutes.

[0093] i) Molecular weight characteristics The number average molecular weight (Mn), weight average molecular weight (Mw) and polydispersity (Mw / Mn) were determined by gel permeation chromatography (GPC) according to the following method.

[0094] Weight average molecular weight Mw and polydispersity (Mw / Mn), where Mn is the number average molecular weight and Mw is the weight average molecular weight, are measured by methods based on ISO 16014-1:2003 and ISO 16014-4:2003. A Waters Alliance GPCV 2000 instrument equipped with a refractive index detector and an online viscometer was used with a 3×TSK-gel column (GMHXL-HT) from TosoHaas and 1,2,4-trichlorobenzene (TCB, stabilized with 200 mg / L of 2,6-ditertbutyl-4-methyl-phenol) as solvent at a constant flow rate of 1 mL / min at 145°C. 216.5 μl of sample solution was injected per analysis. The column set was calibrated using a relative calibration with 19 narrow MWD polystyrene (PS) standards ranging from 0.5 kg / mol to 11500 kg / mol and a set of well-characterized broad MWD polypropylene standards. All samples were prepared by dissolving 5–10 mg of polymer in 10 mL (at 160 °C) of stabilized TCB (same as the mobile phase) and holding for 3 h with continuous shaking before sampling into the GPC instrument.

[0095] h) Sealing behavior The sealing behavior of the coatings was determined by measuring the hot tack force as follows. The maximum hot tack force, i.e. the maximum value on the force / temperature diagram, was determined and reported. Hot tack measurements were performed on a J&B hot tack tester according to the method of ASTM F 1921. This standard requires the specimens to be cut to a width of 15 mm. The specimens are placed vertically in the hot tack tester and attached to mechanical locks at both ends. They are then sealed in the tester, the hot seal is pulled out, and its resistance force is measured. The sealing parameters were as follows:

[0096] [Table 1] EXAMPLES

[0097] A propylene random copolymer according to the present invention using a single-site metallocene catalyst (Invention Example 1, IE1) was prepared as follows. Catalytic system IE1: Metallocene (MC1) (rac-antidimethylsilanediyl(2-methyl-4-phenyl-5-methoxy-6-tert-butyl-indenyl)(2-methyl-4-(4-tert-butylphenyl)indenyl)zirconium dichloride)

[0098] [ka]

[0099] was synthesized according to the procedure described in WO 2013 / 007650E2.

[0100] The MAO-silica support was prepared as follows: A steel reactor equipped with a mechanical stirrer and a filter net was flushed with nitrogen and the reactor temperature was set at 20°C. Then, silica grade DM-L-303 (AGC Si-Tech Co) (7.4 kg), pre-calcined at 600°C, was added from a feed drum, followed by careful pressurization and depressurization with nitrogen using a manual valve. Then, toluene (32 kg) was added. This mixture was stirred for 15 minutes. Then, a 30 wt% solution of MAO in toluene (Lanxess) (17.5 kg) was added through a feed line at the top of the reactor within 70 minutes. The reaction mixture was then heated to 90°C and stirred at 90°C for an additional 2 hours. The slurry was allowed to settle and the mother liquor was filtered. The MAO-treated support was washed twice with toluene (32 kg) at 90°C, then settled and filtered. The reactor was cooled to 60°C and the solid was washed with heptane (32.2 kg). Finally, the MAO-treated SiO 2 The MAO-treated support was recovered as a free-flowing white powder that was found to contain 12.6 wt% Al.

[0101] The final catalyst system was prepared as follows: 30 wt% MAO in toluene (2.2 kg) was added via burette to a steel nitrogen-blanked reactor at 20°C. Toluene (7 kg) was then added with stirring. Metallocene MC1 (286 g) was added from a metal cylinder, followed by a 1 kg toluene rinse. The mixture was stirred at 20°C for 60 minutes. Trityl tetrakis(pentafluorophenyl)borate (336 g) was then added from a metal cylinder, followed by a 1 kg toluene rinse. The mixture was stirred for 1 hour at room temperature. The resulting solution was added over 1 hour to the stirred cake of MAO-silica support prepared above. The cake was allowed to stand for 12 hours, followed by N 2 The catalyst was dried at 60° C. under reflux for 2 hours and then under vacuum (−0.5 barg) with stirring for 5 hours. The dried catalyst was sampled in the form of a pink free-flowing powder containing 13.9 wt. % Al and 0.26 wt. % Zr.

[0102] The polymerizations for preparing the inventive random copolymers of IE1 were carried out in a Borstar pilot plant equipped with a two-reactor setup (loop-gas phase reactor (GPR1)) and a prepolymerizer, using the catalyst system as described above.

[0103] The polymerization conditions for IE1 and the final properties of the resins IE1 and CE2 are shown in Table 1.

[0104] [Table 2]

[0105] The CE2 resin corresponds to the ethylene propylene random copolymer prepared with Ziegler-Natta catalysis in IE3 of the referenced EP 2 999 721.

[0106] This polymer powder was mixed with 0.1 wt. % antioxidant (Irgafos 168FF); 0.1 wt. % sterically hindered phenol (Irganox 1010FF); 0.05 wt. % calcium stearate in a co-rotating twin screw extruder Coperion ZSK 57 at 220°C.

[0107] The combined resins of IE1 and CE2 as described above were used to prepare a coating layer on paper by extrusion coating the resin as follows.

[0108] Extrusion coating was performed on a Beloit co-extrusion coating line. The line was equipped with a Peter Cloeren EBR die and a 5-layer feedblock. The die width was 1000 mm, with an optimal working width of 600-800 mm. The design maximum speed of the line was 1000 m / min, and the line speed was maintained at 150 m / min during the production of the test samples.

[0109] In the above coating line, UG kraft paper 70g / m 2 IE1 or CE2 resin disclosed above (Layer 1, 9 g / m2 ) and polypropylene resin WG341C (available from Borealis, density: 910 kg / m 3 , Melt flow rate (230℃ / 2.16kg): 25g / 10min, Melting temperature (DSC) 161℃, Vicat softening temperature A, (10N) 132℃) of layer 2 (9g / m 2 ) was attached to and coated on a paper substrate.

[0110] The temperature of the polymer melt was set at 290°C, and the temperature profile of the extruder was 200-240-290-290°C. The chill roll was matte and its surface temperature was 15°C. The opening of the die used was 0.65 mm, and the nip distance was 180 mm. The molten film first contacted the substrate at +10 mm from the nip to the substrate side. The pressure of the pressure roll was 3.0 kp / cm 2 The line speed was 150 m / min.

[0111] The hot tack of each sample was established by testing the hot tack force over a temperature range from 90°C to the temperature at which the hot tack force was measured to be less than 1 N. The standard requires that at least three parallel measurements be made. The temperature was increased in 10°C or 5°C increments.

[0112] The hot tack force measurements of the IE1 and CE2 coatings are shown in Figures 1 and 2, respectively.

[0113] The SIT and SET values ​​are obtained from hot tack measurements. In this invention, the temperature (°C) at which the hot tack force reaches 2N is defined as the minimum sealing temperature (SIT), and the temperature (°C) at which the hot tack force remains at 2N is defined as the maximum sealing temperature (SET).

[0114] Maximum hot tack strength is defined as the highest strength (N) level in a 20°C interval of the sealing range.

[0115] As can be seen from the data in Figures 1 and 2, the coating prepared with IE1 provides a lower sealing temperature and higher sealing force.

[0116] Furthermore, as can be seen from the data in Table 1, the resin in IE1 has a much lower amount of hexane extractables according to FDA tests (1.1 wt.% vs. 3.5 wt.% for CE2), making it very well suited for any kind of food application.

Claims

1. Melt flow rate (MFR) of 15 to 40 g / 10 min measured according to ISO 1133 2 (230℃ / 2.16kg), Melting temperature T of 115-145° C. measured by DSC according to ISO 11357 m , ・ 13 The number of 2,1 site defects and 3,1 site defects of 0.01 to 1.2 mol % as measured by C NMR, and Flexural modulus of 500-950 MPa determined on injection molded specimens according to ISO 178 A polypropylene composition comprising a propylene random copolymer having the formula:

2. 2. The polypropylene composition of claim 1, wherein the propylene random copolymer has a molecular weight distribution MWD of 2.4 to 5.5 as determined by GPC and / or a hexane extractables content of less than 2.0 wt.% as measured on a 100 μm thick cast film produced on a monolayer cast film line with a melt temperature of 220° C. and a chill roll temperature of 20° C. according to FDA method (federal registration, Title 21, Chapter 1, Part 177, Section 1520, Appendix B).

3. 3. The polypropylene composition according to claim 1 or 2, wherein the propylene random copolymer has a molecular weight distribution MWD of 2.5 to 4.5 as determined by GPC and / or a hexane extractables content of less than 1.5% by weight as measured according to FDA method (federal registration, Title 21, Chapter 1, Part 177, Section 1520, Appendix B) on a 100 μm thick cast film produced on a monolayer cast film line with a melt temperature of 220° C. and a chill roll temperature of 20° C.

4. The propylene random copolymer has a melt flow rate (MFR) of 17 to 35 g / 10 min, as measured according to ISO 1133. 2 (230° C. / 2.16 kg), and / or a melting temperature T of 120-140° C. as determined by DSC according to ISO 11357 m and / or 13 The polypropylene composition according to any one of claims 1 to 3, having a number of 2,1 site defects and 3,1 site defects of 0.1 to 1.0 mol % as measured by C NMR.

5. The polypropylene composition according to any one of claims 1 to 4, wherein the propylene random copolymer is an ethylene propylene random copolymer.

6. The polypropylene composition according to any one of claims 1 to 5, wherein the propylene random copolymer has an ethylene content in the range of 2.0 to 5.5 wt% or in the range of 2.2 to 4.5 wt%.

7. The propylene random copolymer has a crystallization temperature T in the range of 75 to 110° C., as determined by DSC according to ISO 11357. c and / or having a xylene cold soluble (XCS) fraction determined according to ISO 16152 of 0.1 to less than 15 wt.-%.

8. The propylene random copolymer has a crystallization temperature T in the range of 80 to 105° C., as determined by DSC according to ISO 11357. c and / or having a xylene cold soluble (XCS) fraction determined according to ISO 16152 of 0.1 to less than 7.5 wt.-%.

9. 9. The polypropylene composition according to any one of claims 1 to 8, wherein said propylene random copolymer has a flexural modulus determined on injection moulded specimens according to ISO 178 of 600 to 900 MPa.

10. 10. The polypropylene composition according to any one of claims 1 to 9, wherein said random propylene copolymer comprises or consists of two polymer fractions (RACO-1) and (RACO-2), the division between fraction (RACO-1) and fraction (RACO-2) being from 30:70 to 70:

30.

11. A coated article having a coating layer comprising the polypropylene composition according to any one of claims 1 to 10.

12. A method for coating an article, comprising coating the polypropylene composition according to any one of claims 1 to 10 onto the article by extrusion.

13. Use of the polypropylene composition according to any one of claims 1 to 10 for extrusion coating of articles.

14. 14. The method or use of claim 12 or 13, wherein the article is paper, paperboard, a textile substrate, and / or a metal foil.

Citation Information

Patent Citations

  • Propylene copolymer for thin-wall packaging

    EP2999721A1

  • Polypropylene resin composition for extrusion coating

    JP2002363356A

  • Polypropylene resin composition for self-extinguishing molded item and molded item made of the same

    JP2004026968A

  • Polypropylene resin composition for extrusion coating

    JP2006274114A

  • catalyst

    JP2014525950A